In vivo prediction of body composition from the dilution space of the deuterium oxide in two lactating Spanish dairy breed ewes - Castrillo C.; Dapoza C.; Baucells M.; Bravo M.V.; Ovejero J. (Body condition of sheep and goats: Methodological aspects and applications, 1995)
Thirteen Churra (5 forty days and 8 seventy days after lambing) and twelve Latxa (6 forty days and 6 a hundred and twenty days after lambing) lactating dairy ewes were used to obtain predicting equations of body fat, protein and energy from the live weight and the dilution space of deuterium oxide (SD2O). Churra ewes presented 2 per cent more water and 1.7 per cent less protein in the fat tree empty body 40 days than 70 days after lambing (P less than 0.01) and fat free empty body water content decreased linearly (R
Seminar of the Working Group on Body Condition of Sheep and Goats of the FAO/CIHEAM Network on Sheep and Goats, 24-31 Mar 1994, Zaragoza (Spain)